2017
DOI: 10.1039/c6nr09613a
|View full text |Cite
|
Sign up to set email alerts
|

K-ion and Na-ion storage performances of Co3O4–Fe2O3nanoparticle-decorated super P carbon black prepared by a ball milling process

Abstract: The hybridisation of CoO and FeO nanoparticles dispersed in a super P carbon matrix is proposed as a favourable approach to improve the electrochemical performance (reversible capacity, cycling stability and rate capability) of the metal oxide electrodes in metal-ion batteries. Hybrid CoO-FeO/C is prepared by a simple, cheap and easily scalable molten salt method combined with ball-milling and used in sodium-ion and potassium-ion batteries for the first time. The electrode exhibits excellent cycling stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 58 publications
3
102
0
Order By: Relevance
“…All the electrodes use DME-KFSI as electrolyte at 100 mAh g −1 for measurement. [24,25,[44][45][46][47][48][49][50][51] It is found that our Sb 2 O 3 -RGO composite shows a better K-ion storage performance than other metallic oxide-based materials for KIBs. Compared with Sb 2 O 3 electrode, RGO electrode exhibits the initial reversible specific capacity of 207 mAh g −1 and maintains a reversible specific capacity of 208 mAh g −1 after 50 cycles, owning to its excellent stability and conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…All the electrodes use DME-KFSI as electrolyte at 100 mAh g −1 for measurement. [24,25,[44][45][46][47][48][49][50][51] It is found that our Sb 2 O 3 -RGO composite shows a better K-ion storage performance than other metallic oxide-based materials for KIBs. Compared with Sb 2 O 3 electrode, RGO electrode exhibits the initial reversible specific capacity of 207 mAh g −1 and maintains a reversible specific capacity of 208 mAh g −1 after 50 cycles, owning to its excellent stability and conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[79] Recently, the use of a composite Co 3 O 4 -Fe 2 O 3 as a conversion anode for KIBs was demonstrated. [80] The Co 3 O 4 -Fe 2 O 3 nanoparticles dispersed in a Super P carbon matrix were prepared by magneto-ball-milling of molten-salt-synthesized nanoparticles of Co 3 O 4 and Fe 2 O 3 with Super P carbon black under a controlled atmosphere. This composite anode exhibited a reversible capacity of 220 mA h g −1 at 50 mA g −1 for 50 cycles, which is lower than that achieved for a similar material within Na cells (440 mA h g −1 ).…”
Section: Conversion Anodesmentioning
confidence: 99%
“…Whilst major breakthroughs have been reported in the use of graphite 24 , phosphorus 25 , oxides (such as K 2 Ti 8 O 17 26 , K 2 Ti 4 O 9 27 , Co 3 O 4 -Fe 2 O 3 composites 28 , etc.) and sulphides (namely, MoS 2 29 and SnS 2 30 ) as anode materials, identifying cathode frameworks that can facilitate reversible K-ion insertion is a daunting challenge.…”
Section: Introductionmentioning
confidence: 99%